2022
DOI: 10.14710/jkt.v25i3.15562
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Bioactive Compounds of Tropical Brown Algae Padina sp. from Bintan Island, Indonesia

Abstract: Macroalgae is one of the marine resources that have the ability as an antioxidant. Its ability is obtained from bioactive compounds produced through secondary metabolism. One type of macroalgae that has the potential as an antioxidant is Padina sp. This study aims to analyze the content of bioactive compounds in Padina sp and determine their antioxidant activity using DPPH as free radicals. Padina sp. was taken from the Bintan waters and shade-dried for three days. Bioactive compounds were analyzed through phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The use of polar solvents causes this because, generally, chlorophyll and carotenoids are semipolar compounds, so they dissolve more easily in solvents that have the same polarity. In accordance with the statement that chlorophyll and carotenoids are more easily dissolved in semi-polar solvents [8]. Pigment is an antioxidant because it contains chlorophyll, which can reduce free radicals [16].…”
Section: Pigments Contentmentioning
confidence: 57%
See 1 more Smart Citation
“…The use of polar solvents causes this because, generally, chlorophyll and carotenoids are semipolar compounds, so they dissolve more easily in solvents that have the same polarity. In accordance with the statement that chlorophyll and carotenoids are more easily dissolved in semi-polar solvents [8]. Pigment is an antioxidant because it contains chlorophyll, which can reduce free radicals [16].…”
Section: Pigments Contentmentioning
confidence: 57%
“…Pigment is an antioxidant because it contains chlorophyll, which can reduce free radicals [16]. Apart from chlorophyll, there are carotenoids that have antioxidant capabilities as single oxygen reducers through conjugate bonds in the carbon chain [8].…”
Section: Pigments Contentmentioning
confidence: 99%
“…Three milliliters of a 0.1 mM DPPH solution were added to one milliliter of each concentration. The solution was incubated for 55 minutes [23] before the absorbance of the mixture was determined at the DPPH maximal wavelength (515.5 nm) [23].…”
Section: Antioxidant Activity Measurementmentioning
confidence: 99%
“…While the flavonoid content produced is lower when compared to brown seaweed of the Padina sp. 35.36 mg/QE g of flavonoids [23]. This difference in total phenol and flavonoid content will affect the antioxidant ability of the sample.…”
Section: Bioactive Compounds Of Gracilaria Spmentioning
confidence: 99%
“…[ 8 ] However, none of the reported studies evaluate the algae effect on PMN. [ 9 10 ] Thus, the study reported herein had the objective to examine in vivo the activity of red algae on wound healing by observing the cell viability of PMN.…”
Section: Introductionmentioning
confidence: 99%